(untitled) (Universal International Scientific Journal, 2026)
The article explains that the consistent implementation of social reforms in New Uzbekistan allows for the formation of a socially oriented market economy, the specific features of conducting a clearly targeted, social policy and developing the social sphere, social protection of the population in poverty reduction, the development of entrepreneurship and the effective use of human capital, the extreme urgency of paying special attention to the local, national and regional aspects of this problem, which has raised it to the level of priority policy of our state. The philosophical aspects of creating an active social protection system aimed at reducing poverty in New Uzbekistan, the social significance of creating an active entrepreneurial environment in poverty reduction and the formation of a business mindset, and the possibilities of effective use of human capital in poverty reduction in New Uzbekistan are analyzed.